Evaluation of the influence of contextual factors on the interactions with applications for smartphones - Kronbauer, Artur Henrique; Santos, Celso Alberto Saibel (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
The development of methodologies and techniques to evaluate smartphones usability is an emerging topic in the scientific community and triggers discussions about which methodology is most appropriate. The lack of consensus is due to the inherent difficulty on capturing context data in the scenarios where the experiments take place and on relating them to the found results. This work aims to correlate potential usability problems in mobile applications with contextual factors that may occur during users interactions on different devices, such as: environment luminosity, device screen resolution, and the user's activity while interacting with the application. The following methodology was applied to carry out a field experiment: (1) identification of contextual factors that may influence users' interaction; (2) use of UXEProject Infrastructure to support the automatic capture of applications' context data, by monitoring and storing quantitative, subjective and contextual data from applications' use; (3) implementation of experiments with real users, which have different profiles, on using three different mobile applications over an one year period. In this paper, we present and discuss the results obtained during this study.